Medicinal Plant’s Potential Activity against Skin Disease-causing Bacteria and their Phytochemical Assessment: Medicinal Plant’s Potential Activity against Skin Disease-causing Bacteria and their Phytochemical Assessment - Srivastava, Anshu (International Journal of Pharmaceutical & Biological Archive, 2018)
Plants are the oldest remedies to cure ailments of mankind. They are a storehouse of bioactive compounds which serve as a lead for the development of therapeutics against many diseases including skin diseases. In the present study, leaf extracts of Aegle marmelos, Nerium indicum, Ricinus communis, and Ziziphus nummularia were selected and tested against common skin pathogens, namely Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The methanolic extracts of all the four plants were subjected to an assay for antibacterial activity and minimum inhibitory concentration. As antioxidants play a significant role in skin disease treatments, all the extracts were also evaluated for their antioxidant activity. Preliminary phytochemical screening and estimation of total phenolic content were carried out to establish its correlation with All the methanolic extracts showed good activity against the selected skin pathogens with significant minimum inhibitory concentration (MIC) values. N. indicum and A. marmelos showed the highest zone of inhibition against all tested organisms. The extracts possessed potential antioxidant activity against reactive oxygen species with N. indicum exhibiting most potent activity. Further, preliminary phytochemical screening indicated presence high amount of alkaloids, terpenoids, flavonoids, tannins, and saponins in A. marmelos and N. indicum. R. communis and Z. nummularia had the highest amount of phenolic content. The results of the study indicate that traditional knowledge can serve as a guideline to provide leads for further testing of potentially interesting plants to be used as modern treatment alternatives.